Experimental Verification of the Allelomimesis Clustering Model - Juanico, Dranreb Earl; Saloma, Caesar (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The allelomimesis clustering model is based on only two parameters a and p, which represent the probability of nearest-neighbor copying and the fraction of unresponsive agents, respectively. The model results into the formation of clusters of agents, the sizes of which obey a distribution that is determined by the values of a and p. Several experimental data are fitted by tuning the two parameters. In particular, the significance of the value of a that corresponds to an experimental data is discussed and justified according to ecological context. Recommendations for possible extensions of the model are also enumerated.